2014
DOI: 10.1021/bi500013w
|View full text |Cite
|
Sign up to set email alerts
|

Cancer/Testis Antigen PAGE4, a Regulator of c-Jun Transactivation, Is Phosphorylated by Homeodomain-Interacting Protein Kinase 1, a Component of the Stress-Response Pathway

Abstract: Prostate-associated gene 4 (PAGE4) is a cancer/testis antigen that is typically restricted to the testicular germ cells but is aberrantly expressed in cancer. Furthermore, PAGE4 is developmentally regulated with dynamic expression patterns in the developing prostate and is also a stress-response protein that is upregulated in response to cellular stress. PAGE4 interacts with c-Jun, which is activated by the stress-response kinase JNK1, and plays an important role in the development and pathology of the prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 67 publications
(126 reference statements)
5
74
0
Order By: Relevance
“…Thus, the population of transient turn-like structures increases upon phosphorylation in an ∟20-residue acidic region centered on T51. Further, consistent with our single-molecule fluorescence resonance energy transfer (smFRET) microscopy results (37), this central region becomes more compact and more negatively charged upon phosphorylation with increasing intramolecular contacts to basic sequence motifs near the N and C termini. Furthermore, we observed that although flexibility is decreased in the central region of the phosphorylated ensemble, the polypeptide chain remains disordered and highly dynamic overall.…”
Section: Significancesupporting
confidence: 85%
See 4 more Smart Citations
“…Thus, the population of transient turn-like structures increases upon phosphorylation in an ∟20-residue acidic region centered on T51. Further, consistent with our single-molecule fluorescence resonance energy transfer (smFRET) microscopy results (37), this central region becomes more compact and more negatively charged upon phosphorylation with increasing intramolecular contacts to basic sequence motifs near the N and C termini. Furthermore, we observed that although flexibility is decreased in the central region of the phosphorylated ensemble, the polypeptide chain remains disordered and highly dynamic overall.…”
Section: Significancesupporting
confidence: 85%
“…2B), HIPK1 protein was detected at almost the same level in BPH-1 cells and in the LNCaP cells that are androgen-dependent and nonaggressive, as well as in the androgen-independent and aggressive DU145 and PC3 cells. In contrast, CLK2 was expressed only in In contrast, the dualspecificity kinase CLK2 hyperphosphorylates PAGE4 at eight different S/T residues, including S9 and S51, leading to a more random-like PAGE4 ensemble that attenuates c-Jun transactivation and is likely to be degraded rapidly (9,37,77). Differential phosphorylation of PAGE4 by HIPK1 and CLK2 results in oscillations of the levels of HIPK1-PAGE4, CLK2-PAGE4, and CLK2 that can be modeled mathematically to correlate with the experimentally observed heterogeneity in a population of isogenic PCa cells (details are provided in the main text).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations